A World on Fire, Markets in Turmoil: Uncovering the Resilience of Islamic Stocks Amid Global Conflict - Hasyim, Fuad; Sukardi, Budi; Astuti, Yuni (UIN Kiai Ageng Muhammad Besari Ponorogo, 2025)
Introduction: Geopolitical conflicts that have occurred since 2023, especially between Israel and Palestine, and Israel and Iran, have created significant pressure on global financial market stability. This study evaluates and compares the response and volatility of Islamic stock indices (the Dow Jones Islamic Market) and conventional stock indices (the MSCI World) to those of two major geopolitical events. Research Methods: Using the event-based EGARCH(1,1) model and daily data for the period from January 2023 to June 2025, this study also included macroeconomic control variables such as VIX, USDX, gold prices, and oil prices in the analysis. Results:The results show that DJIM tends to be more responsive to global risk indicators (such as VIX and USDX), but relatively stable to the direct impact of conflict, while the MSCI World shows greater sensitivity to oil price fluctuations. Both indices show persistent and asymmetric volatilities. However, DJIM exhibits a stronger stability in the face of external uncertainty. Conclusion: This study makes an important contribution to the understanding of the resilience of the Sharia market and offers a new methodological approach for examining the dynamics of global conflict. These findings are relevant for investors, regulators, and policymakers to build more resilient and ethical investment strategies.